ANTI-VASCULAR ENDOTHELIAL GROWTH FACTOR PADA RETINOPATHY OF PREMATURITY - Nasyayya Akbari Nazar (Universitas Fort De Kock, 2021)
Introduction: Vascular endothelial growth factor (VEGF) is an important mediator of pathological neovascularization and ocular vascular permeability. In phase I ROP, VEGF levels decrease due to hyperoxia but increase sharply in phase II ROP due to hypoxia, which triggers retinal neovascularization. Purpose: To increase understanding of anti-VEGF injection therapy as a management for ROP in order to avoid serious complications such as blindness in children. Result: The use of intravitreal therapy targeting VEGF is increasingly in demand and has changed the way of view in treating vitreoretinal disease in children, especially in cases with severe posterior abnormalities, media opacity, and unstable systemic Compared with laser, anti-VEGFallows retinal vasculature to further vascularize toward the peripheral retina. Conclusion: Although it has many advantages, it is necessary to have a good understanding and continuous observation of systemic side effects and long-term neurodevelopment in children after anti-VEGF injection given that this action is a new therapy compared to others.